2012
DOI: 10.1111/j.1758-5740.2012.00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Rotator Cuff Responses to Extracorporeal Shockwave Therapy: Morphological and Immunohistochemical Analysis

Abstract: Background Application of extracorporeal shockwave therapy (ESWT) induces an improvement in tissue healing associated with augmented tissue perfusion. The present study aimed to investigate the responses of human rotator cuff tissue to the application of ESWT. Methods Thirty‐one consecutive patients with symptomatic rotator cuff tendinopathy with complete tears were approached and enrolled in the present study. Before surgical resolution, a single treatment of focused ESWT was offered to all patients. Ten p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
0
10
0
2
Order By: Relevance
“…An interesting clinical study by Brañes et al . reported positive effects of ESWT on the angiogenesis but also evaluated effects of shock wave therapy on lymph vessel formation.…”
Section: Potential Mechanism Of Shock Wave Therapymentioning
confidence: 99%
“…An interesting clinical study by Brañes et al . reported positive effects of ESWT on the angiogenesis but also evaluated effects of shock wave therapy on lymph vessel formation.…”
Section: Potential Mechanism Of Shock Wave Therapymentioning
confidence: 99%
“…However, due to physical attributes, radial pressure waves are differing significantly from shockwaves and do not meet the benefits of focused ESWT [ 11 ]. Brañes et al presented improved neovascularization and neolymphangiogenesis after rotator cuff repair in ESWT treated patients [ 38 ]. Recently, clear biomechanical and functional improvements in ESWT treated male Sprague-Dawley rats after repair of chronic rotator cuff tears have been shown [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been proved that the biological effects are related to the pressure wave from [ 30 ]. BrañEs et al [ 31 ] proved that F-SWT was associated with increased neovascularization in rotator cuff tendinopathies. Tei et al [ 32 ] showed that CD34+ mononuclear cells were able to incorporate into neoangiogenic foci and participated in ligament tissue repair.…”
Section: Discussionmentioning
confidence: 99%